Targeted removal of aluminium and copper in Li-ion battery waste solutions by selective precipitation as valuable porous materials - Cognet, Marine (2020)
End-of life Li-ion batteries can be a source of valuable materials to rebuild new batteries or for other applications. In this way, we propose to precipitate metals from a dissolution solution of Li-ions batteries (LiBs) as hybrid organic–inorganic materials (metal–organic frameworks, MOFs), well known in many fields due to their specific properties (high porosity, large surface area and sometimes thermal and chemical stability). From raw LiBs containing Al, Cu, Mn, Ni, or Co mainly, a selective precipitation of different metals as MOFs has been possible. The use of a carboxylate ligand allowed complete precipitation of Al from the solution, whereas using a bipyridine ligand changes the selectivity to precipitate Cu as MOFs. This work shows that formation of different MOFs in a multi-metallic solution can be obtained depending on the precipitating agent.